LOW MOLECULAR METABOLITES OF FUNGI. 3-METOXYSTACHIBOTRINIS STACHYBOTRYS CHARTARUM - Lukhmon Kamolov; Suvonqul Nurmonov; Sevara Tojiyeva (International Engineering Journal For Research & Development, 2021)
Stachybotrys chartarum produces a number of low molecular weight compounds. Column chromatography of the latter isolated the nitrogen-containing compound 3-methoxystachibotrin. The structure of 3-methoxystachibotrin was established on the basis of chemical transformations using the data of ЯМР 1H, 13C, 2М ЯМР 1H-1H, 1H -13C chemical shift correlations (COSY), long-range 1H -13C interaction (НМВС) correlation, NOE measurements in a rotating coordinate system (ROESY), IR and mass- spectra of electron impact.